Integrated Marketing Communication Strategy of PLN UP3 Bandung in the Use of The PLN Mobile Application - Yuhanida Ramadanty; Maylanny Christin (PT Mattawang Mediatama Solution, 2023)
The emergence of PLN Mobile is the answer to PLN UP3 Bandung's innovation to speed up service. In the period 2010-2020 PLN customers increased by 79 million customers and users of the PLN Mobile application from 2021-2022 increased significantly. This study aims to analyze the integrated marketing communication strategy of PLN UP3 Bandung in the use of the PLN Mobile application using the integrated marketing communication strategy concept of William G. Nickles. The research method used is descriptive qualitative with post-positivism paradigm and data triangulation method. The results showed that PLN UP3 Bandung implemented the five integrated marketing communication strategy indicators very well. On the direct marketing indicator, PLN UP3 Bandung is very aggressive and massively participates in activities that invite large crowds, conducts outreach to all groups, and does not carry out marketing activities that disturb customer privacy. On the sales promotion indicator, PLN UP3 Bandung chose a promotional strategy using a referral code and issuing discounts to take advantage of certain moments. On the public relations indicator, PLN UP3 Bandung collaborates with parties such as radio, proliga volleyball, the Bandung Regency Government and the West Java Provincial Government. On the personal selling indicator PLN UP3 Bandung prepares its members before going into the field. On the advertising indicator, all visual and audio-visual content published is clear, straightforward, informative and interesting. PLN UP3 Bandung also carried out good event marketing activities by attending the Proliga volleyball league event, the Anniversary of Bandung City, and the Anniversary of West Java Province